الضغوط المهنية وعلاقتها بالفعالية التنظيمية - كير، سامية, مازوزي، مسعودة (جامعة الوادي university of Eloued, 2021)
الملخص: هدفت الدراسةالحالية إلى التعرف على طبيعة العلاقة بين الضغوط المهنية والفعالية التنظيمية وذلك انطلاقا من التساؤل العام الذي تم طرحه كالآتي : ما طبيعة العلاقة بين الضغوط المهنية والفعالية التنظيمية لدى عمال جامعة الوادي؟ ويندرج تحت هذا التساؤل الأسئلة الفرعية التالية : - ماطبيعة العلاقة بين الضغوط المهنية الفردية و الفعالية التنظيمية لدى موظفي جامعةالوادي؟ - ماطبيعة العلاقة بين الضغوط المهنية التنظيمية والفعالية التنظيمية لدى موظفي جامعةالوادي؟ - ماطبيعة العلاقة بين البيئة الداخلية والفعالية التنظيمية لدى موظفي جامعةالوادي؟ وتكمن أهمية هذه الدراسة في : - محاولة الكشف عن واقع الضغوط التي يعاني منها العمال في جامعة الوادي. - المساهمة في إثراء المكتبة الجامعية بهذا الموضوع الذي يعتبر إضافة في الحقل العلمي الأكاديمي لتقديم دراسات مماثلة. - هذا النوع من الدراسات يسهم بقدر واف على معرفة خصائص وأسباب هذه الضغوط. وقد تم اللجوء إلى المنهج الوصفي, فضلا عن استخدامالاستبيانفيجمعالبياناتمنالميدانوالذيتضمن28 سؤالاحيث تم تطبيق الدراسة على عينة طبقيةمنتظمة تقدر بـ : (58 موظف) من عمال جامعة الوادي. وتوصلت الدراسة إلى النتائج التالية: - وجود علاقة قوية بين الضغوط المهنية الفردية, البيئة الداخلية والفعالية التنظيمية لعمال جامعة الشهيد حمه لخضر بالوادي. - وجود علاقة ضعيفة بين الضغوط المهنية التنظيمية والفعالية التنظيمية لعمال جامعة الشهيد حمه لخضر بالوادي. - وجود علاقة قوية بين الضغوط المهنية والفعالية التنظيمية لعمال جامعة الشهيد حمه لخضر بالوادي. Résumé :فرنسية أو انجلزية The present study aimed to identify the nature of the relationship between the occupational pressures and organizational effectivenessand has been drafted to the question that put forward as follows: Whatis the nature of the relationshipbetweenoccupational stress and organizationaleffectivenessworkers of university EL-OUED ? falls under this sub questions according to following : - What is the nature of the relationship between individual occupational stress and organizational effectiveness workers of university EL-OUED ? - What is the nature of the relationship between organizational occupational stress and organizational effectiveness workers of university EL-OUED ? - What is the nature of the relationship between the internal environment and organizational effectiveness workers of university EL-OUED ? The importance of thisstudy lies in: - An attempt to reveal the reality of the pressures experienced by workersof university EL-OUED. - Contribute to enriching the university library with this topic, which is an addition to the academic scientific field to provide similar studies. - This type of study contributes adequately to the knowledge of the characteristics and causes of these pressures. The descriptive method was usedas well as the use of the questionnaire in the data collection from the field which ensure that (28 Question) Where the study was applied to a systematic stratified sample estimated at: (58 employees) from the university EL-OUED. The study reached the following results: - There is a strong relationship between individual occupational pressures, the internal environment and the organizational effectiveness of the workers of the University EL-OUED. -There is a weak relationship between organizational occupational pressures and organizational effectiveness of the workers of the University EL-OUED. -There is a strongrelationshipbetweenprofessional pressure and organizationaleffectivenessof the workers of the University EL-OUED.
دراسة ميدانية على عينة من عمال جامعة الشهيد حمه لخضر بالوادي
مذكرة ماستر علم الاجتماع تخصص تنظيم وعمل
Keywords: الضغوط المهنية، الفعالية التنظيمية; Pressions professionnelles, efficacité organisationnelle; Occupational pressures, organizational effectiveness